Exploration of Students’ Scientific Argumentation Skills on Static Fluid Topics - Fernando, Trio Junira; Parno, Parno; Diantoro, Markus (Pascasarjana Universitas Negeri Malang (UM), 2024)
The weakness in students’ scientific argumentation, particularly in providing evidence-based arguments, has become a significant concern in education. This study aims to assess students’ scientific argumentation skills specifically on the topic of static fluids. The survey was conducted with 78 twelfth-grade students from private high schools in East Java, Indonesia, who had previously studied this topic. A scientific argumentation test instrument, consisting of an essay format with five questions, was employed to collect data. The data were analyzed using descriptive statistics, followed by a classification based on static fluid subtopics and the level of scientific argumentation skill. The results indicated that the average student score was 10.60, which falls within a low category. Additionally, the findings revealed that a substantial number of students failed to sufficiently use evidence to support their arguments. These outcomes highlight the need for instructional strategies that better develop students’ scientific argumentation skills.DOI: 10.17977/jps.v12i32024p104